Acarofauna asociada a la hojarasca monoespecifica de «peumo» y «boldo» - Salazar Martínez, Ana Ernestina (1996)
The objective of this study is to estimate the existence of a characteristic set of acari associated to monospecific litter of «peumo» and «boldo». The experimental design included the instalation of nylon bag of mesh size of 15 mm, with senescent leafs of peumo and boldo plucked from trees, and with 23 recolections made during three years. In each recolection six bags with «peumo», six with «boldo», and three with leaf litter (witness litter) were retrieved from the field. The acari were extracted through Berlese funnels during ten days. Differences among acarological sets are quantitatively denoted by the alterations in abundance and morphospecific diversity. At a qualitative level, the morphospecific structure differed in the scarce morphospecies. Taking into account its abundance, the important morphospecies were defined as preferent to litter: Ascidae sp., Eupodidae sp., Glycyphagus sp., Liochthonius sp., and Oppia sp. 2 were associated to «boldo», whereas C. porula, Rhyzoglyphus sp., and Histiostoma sp. were associated to «peumo».